Search for the decay of a Higgs boson in the $\ell\ellγ$ channel in proton-proton collisions at $\sqrt{s} =$ 13 TeV - CMS collaboration (2301 authors) (2018)
A search for a Higgs boson decaying into a pair of electrons or muons and a photon is described. Higgs boson decays to a Z boson and a photon (H $→$ Z$γ→\ell\ellγ$, $\ell =$ e or $μ$), or to two photons, one of which has an internal conversion into a muon pair (H $→γ^{*}γ→μμγ$) were considered. The analysis is performed using a data set recorded by the CMS experiment at the LHC from proton-proton collisions at a center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 35.9 fb$^{-1}$. No significant excess above the background prediction has been found. Limits are set on the cross section for a standard model Higgs boson decaying to opposite-sign electron or muon pairs and a photon. The observed limits on cross section times the corresponding branching fractions vary between 1.4 and 4.0 (6.1 and 11.4) times the standard model cross section for H $→γ^{*}γ→μμγ$ (H $→$ Z$γ→\ell\ellγ$) in the 120-130 GeV mass range of the $\ell\ellγ$ system. The H $→γ^*γ→μμγ$ and H $→$ Z$γ→\ell\ellγ$ analyses are combined for $m_H =$ 125 GeV, obtaining an observed (expected) 95% confidence level upper limit of 3.9 (2.0) times the standard model cross section.